Digitalisation in Civil Law: Digital Reputation - Sarina, Salima; Adilova, Kultay; Aralbayeva, Aigerim; Kurmanaliyeva, Elmira; Teleuyev, Galym (Law, State and Telecommunications Review, 2025)
[Purpose] The study aims to explore new aspects of digitalisation, the formation of a legal regime for the use of services for the preservation and transmission of information and their impact on digital reputation. [Methodology/approach/design] The main methods of research were analysis and synthesis, dialectical method, method of deduction and generalisation. Alternative approaches to the preservation and transmission of information that affect the digital reputation of citizens are emphasised. [Findings] The directions of the development of legislation for the formation of civil society’s reputation to digital services and legal regime, as well as effective mechanisms for the use, transfer and preservation of information in the field of civil law are determined. The quality of digital services for the citizens of the Republic of Kazakhstan, as well as their legal protection in the field of informatisation, is addressed in this study. A brief review of international acts in the information sphere and their application in foreign countries in the context of human rights protection in the conditions of digital transformation was made. Measures that are taken to increase the digital trust of citizens in the course of the introduction of new technologies into public life were considered. [Practical implications] The results of the study may be useful in the development of new norms of civil law by responsible officials taking into account the introduction of new technologies to ensure effective digitalisation of all processes in society, which will increase trust in innovative processes in society and thus affect the digital reputation in general.